Adult nutrition affects reproduction and flight performance of the invasive fall armyworm, Spodoptera frugiperda in China - Li-mei HE; Shan JIANG; Yu-chao CHEN; Kris A.G. WYCKHUYS; Shi-shuai GE; Wei HE; Xi-wu GAO; Kong-ming WU (Journal of Integrative Agriculture, 2021)
Floral resources, such as carbohydrate-rich nectar or pollen, can bolster fitness and raise reproductive output of adult lepidopterans. Here, we used laboratory experiments to assess how those plant-derived foods impact adult fecundity, reproductive physiology and flight performance of an invasive strain of the fall armyworm, Spodoptera frugiperda (FAW; Lepidoptera: Noctuidae) in China. More specifically, supplementary feeding on bee pollen and honey enhanced FAW flight duration, testis size, ovarian development, longevity and adult fecundity. FAW adults attained the longest pre-oviposition (10.8 days) and oviposition period (6.8 days) and longevity (19.2 days) on 5% acacia honey. Upon access to 2.5% acacia honey and 2.5‰ pine pollen, S. frugiperda attained the highest mating rate (79.7%), fecundity (644.9 eggs/female) and egg hatching rate (82.3%). Feeding on honey further delayed decay of male testes, while ovarian development was enhanced when female moths were allowed access to 2.5% honey and 2.5‰ pine pollen. Upon feeding on 5% honey solution, S. frugiperda engaged in flight over the longest duration (9.5 h), distance (29.9 km) and speed (3.1 km h−1). Honey had a comparatively greater effect on the above parameters than pollen. Our findings help decipher FAW invasion patterns and population dynamics, facilitate the development of nutritional attractants, and contribute to integrated pest management of this newly-invasive pest in eastern Asia.